Transcanal Endoscopic Ear Surgery for Pediatric Bilateral Congenital Cholesteatoma: A Report of Two Cases - Takashi Ueda; Takeshi Fujita; Natsumi Uehara; Jun Yokoi; Mitsuko Yui; Ayu Akazawa; Toshihiko Yamashita; Yukako Goto; Akinobu Kakig; Ken-ichi Nibu (Journal of International Advanced Otology)
Bilateral congenital cholesteatoma (BCC) is rare among congenital cholesteatoma (CC) cases, and bilateral surgery poses a significant psychophysical burden on pediatric patients. Here, we present 2 pediatric cases of BCC that were successfully managed using simultaneous bilateral transcanal endoscopic ear surgery (TEES). The surgical approach provided clear visualization of the middle ear structures, enabling successful cholesteatoma removal with minimal invasiveness and a short operative time. In both cases, follow-up computed tomography showed no recurrence, and pure-tone audiometry results demonstrated good outcomes. Simultaneous bilateral TEES can be a viable option for pediatric BCC, as it reduces patient burden due to its less invasive procedure and short operative time.